Nitrogen and sulphur requirements of shattering tolerant canola oilseed rape (Brassica napus L.) under varied plant population: Nitrogen and sulphur requirements of shattering tolerant canola oilseed rape (Brassica napus L.) under varied plant population - VIRENDER SARDANA; S S BANGA; GURPREET KAUR; PUSHP SHARMA (Journal of Oilseeds Research, 2020)
The study was conducted during rabi 2018-19 to study about the row spacing, nitrogen and sulphur requirements of shattering tolerant oilseed rape. Row spacing of 30 cm resulted in 12.7 and 12.6 % higher seed (2819 kg/ha) and oil (1066 kg/ha) yield than 45 cm row spacing. Application of 100 kg/ha of N significantly increased the seed yield by 11.8% and oil yield by 11.9% over 75 kg/ha of N. Application of 40 kg/ha of S increased the seed and oil yield by 3.8% and 4.5%, respectively over 20 kg/ha of applied S. Interactions between different treatments for different traits were non-significant.